Design for BLDC Motor Control System in Flying Electric Vehicle - Muhammad Nurus Syamsi; Sugeng Hadi Susilo (Journal of Evrímata: Engineering and Physics, 2025)
The choice of control system for a flying electric vehicle/quadcopter is very important, especially for users who have never built or driven a flying electric vehicle. Electrical components which include the flight controller, ESC, battery, BLDC motor and other components have an influence in planning electric flying vehicles. Therefore, a BLDC motor control system is needed so that it can operate according to wishes and needs. The purpose of this research is to find out how the control system wiring diagram works, which includes the flight controller wiring diagram as the main flight control and the Electronic Speed ​​Control (ESC) wiring diagram as the BLDC motor speed controller. The choice of flight controller to operate the electric vehicle flight uses DJI Naza M V2 and electronic speed control uses a flier with a 3s-20s cell count configuration.